Identification and preliminary characterization of novel B3-type metallo-β-lactamases - Miraula, Manfredi; Brunton, Conor S.; Schenk, Gerhard; Mitić, Nataša (Scientific Research Publishing, 2013)
Antibiotic resistance has emerged as a major global threat to human health. Among the strategies employed by pathogens to acquire resistance the use of metallo-β-lactamases (MBLs), a family of dinuclear metalloenzymes, is among the most potent. MBLs are subdivided into three groups (i.e. B1, B2 and B3) with most of the virulence factors belonging to the B1 group. The recent discovery of AIM-1, a B3-type MBL, however, has illustrated the potential health threat of this group of MBLs. Here, we employed a bioinformatics approach to identify and characterize novel B3-type MBLs from Novosphingobium pentaromativorans and Simiduia agarivorans. These enzymes may not yet pose a direct risk to human health, but their structures and function may provide important insight into the design and synthesis of a still elusive universal MBL inhibitor.
Keywords: Antibiotic Resistance; β-Lactam Antibiotics; Metallo-β-Lactamases; Sequence Homology; Novosphingobium Pentaromativorans; Simiduia Agarivorans